In The Company Of Women : Contemporary Female Friendship Films - Hollinger, Karen (Book collections on Project MUSE., 1998)
From Desperately Seeking Susan, Steel Magnolias, and Thelma & Louise to Desert Hearts, Girl Friends, and Passion Fish, mainstream cinema has seen a wave of films focusing on friendships between women. In the Company of Women is the first critical work to investigate the recent resurgence of this variety of the "womans film."